1987
DOI: 10.1192/bjp.150.2.235
|View full text |Cite
|
Sign up to set email alerts
|

Life Events and Mania

Abstract: Fifty patients in their first manic episode were compared retrospectively with groups of (a) manic patients in other than first admissions and (b) acute surgical cases. They were then followed up for 3–8 years. First manic admissions were linked to life events far more frequently – 66%vs20% and 8% respectively for the other groups. Within-group comparisons showed patients with life events were much younger. The link between life events and manic episodes appeared immediate and selective, a view further support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Of these, two were chart reviews (Ambelas, 1979, 1987). Ambelas (1979) found that manic patients in their initial hospitalization were significantly more likely to have experienced a pre-admission event in the month prior to admission, as compared to manic patients in a repeat hospitalization.…”
Section: Existing Research On Kindling In Bipolar Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, two were chart reviews (Ambelas, 1979, 1987). Ambelas (1979) found that manic patients in their initial hospitalization were significantly more likely to have experienced a pre-admission event in the month prior to admission, as compared to manic patients in a repeat hospitalization.…”
Section: Existing Research On Kindling In Bipolar Disordermentioning
confidence: 99%
“…Ambelas (1979) found that manic patients in their initial hospitalization were significantly more likely to have experienced a pre-admission event in the month prior to admission, as compared to manic patients in a repeat hospitalization. A follow-up chart review indicated that mean scaled stress scores were significantly higher before first than subsequent admissions (Ambelas, 1987). Perris (1984b) assessed the frequency of life events in the three- and twelve-month intervals prior to onset of a depressive index episode in an inpatient sample with various affective disorder diagnoses.…”
Section: Existing Research On Kindling In Bipolar Disordermentioning
confidence: 99%
“…For example, human beings are subjected to various and variable forms of life stress, which can be approximated as a complex 'noisy environment' interacting with the human organism (Glassner and Haldipur, 1983;Kennedy et al, 1983;Bidzinska, 1984;Ambelas, 1987;Swann et al, 1990;Charney et al, 1993;Castine et al, 1998). In addition, biological systemsFand brains in particularFthemselves are intrinsically noisy.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, at the behavioral level, individuals face a variety of life stress, which differs in strength and impact and reaches from everyday hassles to social isolation up to the loss of significant others. In turn, such life stress might be viewed as a complex variable 'noisy environment' that individuals have to deal with and which will interact with any disease process (Glassner and Haldipur, 1983;Kennedy et al, 1983;Bidzinska, 1984;Ambelas, 1987;Swann et al, 1990;Charney et al, 1993;Castine et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies used cross-sectional designs comparing rates of life events in patients experiencing a first episode versus a recurrence (Ambelas, 1979, 1987; Perris, 1984) or retrospective designs that examined the frequency of life events occurring prior to participants’ earlier vs. later episodes (Bidzinska, 1984; Dunner et al, 1979; Ehnvall & Ågren, 2002; Johnsonet et al, 2000) with some not finding support for a kindling effect in BD (Kennedy et al, 1983; Glassner & Haldipur, 1983). These mixed findings were attributed to long intervals for recall and the use of stress checklists that may be biased by participants’ current mood or fallible memory.…”
Section: The Kindling Hypothesis In Bipolar Disordermentioning
confidence: 99%